A complexa fisiopatologia dos episódios vasooclusivos na anemia falciforme - Silveira, Margarida Maria; Da Fonseca, Luiz Marcos [UNESP] (My University, 2002)
Hemolytic anemia and vasoocclusion are the cardinal clinical features of sickle cell anemia. Vasoocclusion is a complex process involving not only the polymerization of deoxygenated sickle hemoglobin tetramers, but also interactions between sickle erythrocytes, vascular endothelium, platelets, leukocytes, and plasma proteins. The increased adherence of sickle erythrocytes to endothelium has been implicated as an early step in vasoocclusion. Other researchers have focused on leukocytes and platelets which might also contribute to disturbed blood flow. Microvascular occlusion results in acute painful crises, whereas macrovascular occlusion seems to be the cause of organ failure. The anemia results from the markedly shortened circulatory survival of sickle erythrocytes, together with a limited erythropoietic response. The erythropoiesis increases intensively, but it is not enough to balance the increased rate of erythrocytes destruction to maintain normal levels of total erythrocytes and hemoglobin concentrations; mainly by the low oxygen affinity of hemoglobin S and increased 2,3-Diphosphoglycerate. It is very difficult to separate processes leading to anemia or to vasoocclusion. Understanding the involvement of multiple blood componentes in vasoocclusion may elucidate the clinical manifestations and complications of sickle cell anemia, and may give new insights into the preventive and curative therapy.
The complex pathophysiology of the vasoocclusive episodes in the sickle cell anemia
Keywords: Leukocytes; Platelets; Sickle cell anemia; Vasoocclusion; 2,3 diphosphoglyceric acid; hemoglobin S; tetramer; blood component therapy; blood flow velocity; blood oxygenation; blood vessel occlusion; cell adhesion; cell damage; cell interaction; cell survival; circulation time; clinical feature; concentration response; endothelium cell; erythrocyte; erythrocyte adhesiveness; erythrocyte disorder; erythrocyte lifespan; erythropoiesis; hemoglobin analysis; hemolytic anemia; human; leukocyte; multiple organ failure; oxygen affinity; pain; pathophysiology; polymerization; process monitoring; protein blood level; protein structure; review; sickle cell; sickle cell anemia; thrombocyte; vascular endothelium; vein occlusion